The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1021/es034928d
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Emission Benefit of Diesel (versus Gasoline) Powered Vehicles

Abstract: Concerns regarding global warming have increased the pressure on automobile manufacturers to decrease emissions of CO 2 from vehicles. Diesel vehicles have higher fuel economy and lower CO 2 emissions than their gasoline counterparts. Increased penetration of diesel powered vehicles into the market is a possible transition strategy toward a more sustainable transportation system. To facilitate discussions regarding the relative merits of diesel vehicles it is important to have a clear understanding of their CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 4 publications
(11 reference statements)
0
63
0
1
Order By: Relevance
“…Section 6 concludes. rate of a vehicle is proportional to the fuel consumption rate of the vehicle, with the proportionality factor differing across diesel and gasoline engines (Sullivan et al, 2004), so this cutoff is equivalent to 8.4 liters/100 km for gasoline cars and 7.5 liters/100 km for diesel cars.…”
mentioning
confidence: 99%
“…Section 6 concludes. rate of a vehicle is proportional to the fuel consumption rate of the vehicle, with the proportionality factor differing across diesel and gasoline engines (Sullivan et al, 2004), so this cutoff is equivalent to 8.4 liters/100 km for gasoline cars and 7.5 liters/100 km for diesel cars.…”
mentioning
confidence: 99%
“…The CO 2 emissions of the KBA file are used, assuming the same annual mileage for the current and future gasoline and Diesel passenger cars. In a first stage, the CO 2 emissions are calculated using the current data; in a second one, the future CO 2 emissions are estimated taking into account the most probable future technologies (Sullivan et al, 2004). This study is limited to CO 2 emissions from new registered passenger cars.…”
Section: Assumptions and Methodology Usedmentioning
confidence: 99%
“…A previous study (Sullivan et al, 2004), showed a significant decrease of CO 2 emissions in the USA by the introduction of Diesel passenger cars. This study did not take into account a sales-weighted approach.…”
Section: Introductionmentioning
confidence: 93%
“…Assuming a density of 700 kg/m3, 1 kg of gasoline produces 3.42 kg of CO2 (tank to wheel emissions). Sullivan et al 2004 consider a multiplying factor of 1.162 to pass from TTW to WTW emissions of CO2. Thus, a kg of gasoline can be assumed to produce 3.98 kg of CO2 (WTW).…”
Section: Well-to-wheel Emissions Of Co2mentioning
confidence: 99%